Investigating Indonesian Textbooks Readability Using Fry Graph Formula - Sarimanah, Eri; Soeharto, Soeharto; Ramadhanti, Anissa; Suhendra, Suhendra; Efendi, Roy (Universitas Islam Negeri Raden Intan Lampung, 2021)
Learning the Indonesian language cannot be separated from the use of textbooks. In using textbooks, teachers must consider several aspects, especially text readability. This study aims to measure text readability in Indonesian textbooks using the Fry Graph Formula and determine the suitability of the text used in the book with the student's school level. The present study applied the descriptive analysis and quantitative approach method to count and analyze texts in several Indonesian language textbooks readability using the Fry graph formula. Three Indonesian language textbooks with 45 measured text in 11th grade were analyzed. This study found that 25 texts showed the results